Growing Open - Astrid Gynnild (Grounded Theory Review: An International Journal, 2006)
Doing a PhD can principally be carried out in three ways; firstly by applying existing theories on new data, secondly by theoretically comparing existing theories and thirdly by generating a new theory. Choice of approach of course depends on awareness and accessibility of alternatives. In essence, most PhD studies are exploratory journeys in a jungle of descriptive methodologies based on very uniform data. In this paper, the author elaborates the exploratory research process that subconsciously, and later consciously, required a shift from the initial QDA approach to grounded theory. The cutting point was discovering the multifaceted implications of the all-is-data dictum in GT.